2005
DOI: 10.1161/01.atv.0000151279.35780.2d
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor Xa Stimulates Interleukin-8 Release in Endothelial Cells and Mononuclear Leukocytes

Abstract: Objective-In acute myocardial infarction (AMI), proinflammatory plasma C-reactive protein values are strongly associated with postinfarction morbidity and mortality. So far, the cause of these inflammatory changes is not well understood. Therefore, we sought to investigate the relationship between the activation of coagulation and subsequent systemic inflammatory changes in AMI. Methods and Results-Factor Xa (FXa) bound to tissue factor pathway inhibitor and prothrombin fragments F1ϩ2 (F1ϩ2) were used as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 41 publications
4
48
0
1
Order By: Relevance
“…There are two other pathophysiological facets underlining the hypothesis that IL-8 is a potential profibrillatory marker. Firstly, there is a bidirectional link between IL-8 and coagulation (5). IL-8 exerts a procoagulant activity by induction of tissue factor expression in circulating monocytes (37).…”
Section: Il-8mentioning
confidence: 99%
See 1 more Smart Citation
“…There are two other pathophysiological facets underlining the hypothesis that IL-8 is a potential profibrillatory marker. Firstly, there is a bidirectional link between IL-8 and coagulation (5). IL-8 exerts a procoagulant activity by induction of tissue factor expression in circulating monocytes (37).…”
Section: Il-8mentioning
confidence: 99%
“…Formation of intracoronary thrombi during myocardial ischemia requires thrombin which is not only necessary for the coagulation cascade, but also interacts with cardiomyocytes via protease-activating receptors and has arrhythmogenic properties in ventricular myocytes (4). Thrombin also induces interleukin-8 (IL-8) production in endothelial and mononuclear cells probably by this classic thrombin receptor (5). In vitro studies with human whole blood revealed that coagulation activation triggers IL-8 release to be positively correlated with the measurement of thrombin-antithrombin complexes, indicating that IL-8 is a key proinflammatory mediator of the crosstalk between coagulation and inflammation (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Three to four confluent plates (corresponding to 3-4 × 10 5 cells per 100-mm dish) were lysed using TriZol (Invitrogen, Karlsruhe, Germany), and total RNA was extracted with an RNeasy Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions. Reverse transcription and semiquantitative [19] and quantitative PCR [20] were performed as described before. The primers for semiquantitative PCR (GAPDH and IGF-2) were obtained from Applied Biosystems (Darmstadt, Germany) and MWG Biotech (Munich, Germany), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Coagulation factors activate proteaseactivated receptors (PARs) on mononuclear or endothelial cells and thereby contribute to cytokine generation or inflammatory cell apoptosis. 2,3 Elegant experiments in genetically modified mice identified the key role of TF and PARs in coagulation-induced inflammation during endotoxemia. A decrease in TF activity in low TF or a PAR-2 deficiency in combination with thrombin inhibition abrogated systemic inflammatory changes.…”
mentioning
confidence: 99%
“…TF antigen in plasma is found to be elevated in a number of disease states associated with increased activation of the coagulation. 3 However, this circulating extracellular TF consists of 2 forms in addition to soluble secreted TF: truncated forms and procoagulant microparticles (MP). 6 MPs are small membrane vesicles, released from blood cells or endothelial cells on activation by cytokines, shear stress, or apoptosis.…”
mentioning
confidence: 99%